Business Metaphors in a Bilingual Business Lexicon - Lan, Li; Bilbow, Grahame T. (Lexikos, 2002)
Abstract: General purpose dictionaries benefit users at large in many ways, but the definitions and examples might not satisfy the diverse needs of different professional users. This is especially true of metaphors. The article discusses the treatment of business metaphors in the PolyU Business Lexicon derived from the trilingual PolyU Business Corpus (PUBC). During the process the concordances are grouped by senses, and then separated according to their literal and metaphorical meanings, which in turn lead to the decisions of sense order, word meaning and translation equivalents. Since different cultures have different ’bags’ of metaphors, and metaphorical meanings also vary in different registers, the focus is primarily on the differences between Chinese and English in terms of culture, psychology, language and how such differences can be translated and presented in a corpus-based business lexicon with a minimum loss of their original connotations. Cultural transformations, such as direct translation, image substitution, explanatory notes and abandonment of the figure of speech, are suggested to bridge interlanguage metaphorical gaps. Keywords: METAPHOR, DEFINITION, TRANSLATION, CULTURAL DIFFERENCE Opsomming: Sakemetafore in ’n tweetalige sakewoordeboek. Woordeboeke vir algemene doeleindes bevoordeel gewone gebruikers op baie maniere, maar die definisies en voorbeelde mag dalk nie die uiteenlopende behoeftes van verskillende professionele gebruikers bevredig nie. Dit is veral waar van metafore. Die artikel bespreek die behandeling van sakemetafore in die PolyU Business Lexicon gebaseer op die drietalige PolyU Business Corpus (PUBC). Gedurende die proses word die konkordansies deur betekenisse gegroepeer, en dan geskei volgens hul letterlike en metaforiese betekenisse, wat vervolgens lei tot die besluite oor betekenisorde, woordbetekenis, en vertaalsekwivalente. Aangesien verskillende kulture verskillende "sakke" metafore het, en metaforiese betekenisse ook varieer in verskillende registers, is die fokus prim?r op die verskille tussen Sjinees en Engels in terme van kultuur, psigologie, taal en hoe sulke verskille vertaal en aangebied kan word in ’n korpusgebaseerde sakewoordeboek met ’n minimum verlies aan hul oorspronklike konnotasies. Kulturele transformasies, soos direkte vertaling, beeldvervanging, verklarende aantekeninge en prysgewing van die stylfiguur, word voorgestel vir die oorbrugging van die tussentalige metaforiese gapings. Sleutelwoorde: METAFOOR, DEFINISIE, VERTALING, KULTURELE VERSKIL